QUALITY OF LIFE AND FACTORS ASSOCIATED WITH THE LEVEL OF COMMUNITY INTEGRATION AMONG PATIENTS WITH STROKE (Vietnam Journal of Community Medicine, 2026)
Objective: To examine the level of community integration among post-stroke patients after hospital discharge and to investigate the association between quality of life, health behaviors, and community integration at Viet Tiep Friendship Hospital. Methods: A cross-sectional descriptive study was conducted among 126 stroke survivors attending outpatient follow-up clinics between December 1, 2025, and February 1, 2026. Health-related quality of life was assessed using the EQ-5D-5L, while community integration was measured using the Community Integration Questionnaire (CIQ). Independent samples t-tests, one-way ANOVA, and multivariable linear regression analyses were performed to examine factors associated with community integration.Results: The mean community integration score was 26.64 ± 8.03. Among the CIQ domains, family integration had the highest mean score (9.36 ± 3.39), whereas social networking had the lowest mean score (4.42 ± 2.33). Health-related quality of life was significantly associated with community integration (B = 6.937, p = 0.046). In contrast, no significant association was observed between health behaviors and community integration.Conclusion: Stroke survivors had a relatively high score for community integration following hospital discharge. Improving physical functioning, enhancing self-care ability, and promoting health-related quality of life may facilitate community reintegration among stroke survivors.
Keywords: Stroke; Community integration; Quality of life; Health behaviors